2009
DOI: 10.1021/jf901618z
|View full text |Cite
|
Sign up to set email alerts
|

DNA Barcoding of Commercially Important Salmon and Trout Species (Oncorhynchus and Salmo) from North America

Abstract: The present study investigated the ability of DNA barcoding to reliably identify the seven commercially important salmon and trout species (genera Oncorhynchus and Salmo ) in North America. More than 1000 salmonid reference samples were collected from a wide geographic range. DNA extracts from these samples were sequenced for the standard 650 bp barcode region of the cytochrome c oxidase subunit I gene (COI). DNA barcodes showed low intraspecies divergences (mean, 0.26%; range, 0.04-1.09%), and the mean congen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
56
2
5

Year Published

2010
2010
2021
2021

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(66 citation statements)
references
References 28 publications
3
56
2
5
Order By: Relevance
“…The average K2P distance estimate of intraspecies divergence in this study was 0.17% (maximum 1.08%) (see Table II), which is lower than the previous fish DNA barcoding studies, which have reported mean conspecific divergences of 0.27% (range 0-1.95%) for 1035 salmon and trout specimens from North America (Rasmussen et al 2009), 0.30% (range 0-7.42%) for 194 Canadian fish species (Hubert et al 2008), 0.39% (range 0-14.08%) for 207 Australian fish species (Ward et al 2005), and 0.99% (0.19% when possible misidentifications were omitted) for 72 commercial fish species in the USA (Yancy et al 2008). In summary, even with a significant overlap of the genetic distances at the genus level and above (see Table II), the average genetic distance among congeneric species is nearly 60-fold higher than that found within species, a ratio higher than the 12-fold and 27-fold previously reported for freshwater fishes in Mexico/Guatemala (Valdez-Moreno et al 2009) and Canada (Hubert et al 2008), respectively.…”
Section: Minimal Divergence But Phylogeographic Variation Within Speciescontrasting
confidence: 78%
See 1 more Smart Citation
“…The average K2P distance estimate of intraspecies divergence in this study was 0.17% (maximum 1.08%) (see Table II), which is lower than the previous fish DNA barcoding studies, which have reported mean conspecific divergences of 0.27% (range 0-1.95%) for 1035 salmon and trout specimens from North America (Rasmussen et al 2009), 0.30% (range 0-7.42%) for 194 Canadian fish species (Hubert et al 2008), 0.39% (range 0-14.08%) for 207 Australian fish species (Ward et al 2005), and 0.99% (0.19% when possible misidentifications were omitted) for 72 commercial fish species in the USA (Yancy et al 2008). In summary, even with a significant overlap of the genetic distances at the genus level and above (see Table II), the average genetic distance among congeneric species is nearly 60-fold higher than that found within species, a ratio higher than the 12-fold and 27-fold previously reported for freshwater fishes in Mexico/Guatemala (Valdez-Moreno et al 2009) and Canada (Hubert et al 2008), respectively.…”
Section: Minimal Divergence But Phylogeographic Variation Within Speciescontrasting
confidence: 78%
“…In summary, even with a significant overlap of the genetic distances at the genus level and above (see Table II), the average genetic distance among congeneric species is nearly 60-fold higher than that found within species, a ratio higher than the 12-fold and 27-fold previously reported for freshwater fishes in Mexico/Guatemala (Valdez-Moreno et al 2009) and Canada (Hubert et al 2008), respectively. The ratio observed in this study is also much higher than the 25-fold and 26-fold reported for marine salmon and trout (Rasmussen et al 2009) and ornamental marine fishes (Steinke et al 2009b), respectively. Although the primary objective of DNA barcoding is to identify species, phylogeographic structure among COI sequences within species became evident in this study.…”
Section: Minimal Divergence But Phylogeographic Variation Within Speciescontrasting
confidence: 67%
“…Finally, the accuracy of the DNA-based identifications is tightly dependent on the coverage of the DNA barcode reference libraries used to assign the sequences generated through NGS to known taxa [e.g. 17,21,28,189,[205][206][207][208][209].…”
Section: Discussionmentioning
confidence: 99%
“…Researchers have demonstrated that genetic barcoding has been beneficial in population genetic studies on invertebrates [18] [19] [20] and vertebrates [21] [22], such as fish [23] [24] [25]. Barcoding has the ability to detect both interspecies and intraspecies variation [26], [27] whether genetic samples are obtained from larval, juvenile or adult life stages [26] [28] Open Journal of Genetics [29]. The aim of the present study is to identify CO1 haplotypes among black crappie residing in three Georgian lakes (Lake Sidney Lanier, Lake Seminole, and Hartwell Lake) and examine the population structure among species inhabiting the aforementioned water systems utilizing universal barcode COI.…”
mentioning
confidence: 99%